THE EFFECT OF FINANCIAL DISTRESS, PROFITABILITY, LEVERAGE, AND LIQUIDITY ON GOING CONCERN AUDIT OPINION - Yuliyani, Ni Made Ade; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
The purpose of this study was to determine the effect of financial distress, profitability, leverage, and liquidity on a going concern audit opinion. Research was conducted on the Indonesian Stock Exchange (BEI) to make access to the site www.idx.co.id. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2010-2015. The number of manufacturing companies sampled in this study is 25 companies with observation for 6 years. Based on purposive sampling method, the total sample is 150 samples. Methods of data collection in this study using techniques of documentation. Testing the hypothesis in this study using logistic regression analysis. The results showed that the negative impact of financial distress on a going concern audit opinion, while profitability, leverage, and liquidity does not affect the going concern audit opinion
Keywords: Financial Distress, Profitability, Leverage, Liquidity, Going Concern